2022
DOI: 10.2196/30082
|View full text |Cite
|
Sign up to set email alerts
|

Learning Outcomes of Immersive Technologies in Health Care Student Education: Systematic Review of the Literature

Abstract: Background There is a lack of evidence in the literature regarding the learning outcomes of immersive technologies as educational tools for teaching university-level health care students. Objective The aim of this review is to assess the learning outcomes of immersive technologies compared with traditional learning modalities with regard to knowledge and the participants’ learning experience in medical, midwifery, and nursing preclinical university educ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…However, the use of virtual reality in health professions education is gaining ground and is starting to play an important role in competence development. Immersive technologies can provide learning gains similar to those provided by traditional educational modalities [ 10 ]. They can increase attention and enhance skills and confidence and seem to influence users’ emotional responses to learning situations, which in turn increases learning motivation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of virtual reality in health professions education is gaining ground and is starting to play an important role in competence development. Immersive technologies can provide learning gains similar to those provided by traditional educational modalities [ 10 ]. They can increase attention and enhance skills and confidence and seem to influence users’ emotional responses to learning situations, which in turn increases learning motivation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can increase attention and enhance skills and confidence and seem to influence users’ emotional responses to learning situations, which in turn increases learning motivation [ 11 ]. Furthermore, other outcomes, such as student satisfaction, self-efficacy, and engagement, may increase when using such technology, suggesting that it is a viable tool in health professions education [ 10 ]. A systematic review from 2021 examined the use of virtual reality to train nursing students and found it to be a feasible teaching strategy to improve knowledge acquisition when used to supplement, but not replace, conventional teaching methods [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 Studies have found that the risk of HPV infection in humans is very high, and the incidence of cervical HPV infection is more than 80% in sexually active people. 7 In 2018, 106430 new cases of cervical cancer and 47739 deaths were reported in China, accounting for 18.2% and 17.3% of the global incidence and mortality of cervical cancer. 8 According to the 2020 Annual Work Report of National Cancer Center issued by the China National Cancer Center, cervical cancer is the sixth most common tumor with a high incidence in female cancer in China, and its mortality rate is the eighth in female malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…6 During the last decade, stakeholders have brought significant changes in the theoretical basis and teaching approaches of CME, which have modified clinical practices. 7 The physicians learn a lot from the interactive sessions and educational events conducted for CME. 3 Healthcare practitioners in knowledge-intensive industries need lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual reality and other immersive technologies for patient care can be systematized as follows: (3,4,5,6,7,8,9) • The use of virtual reality to provide pain management and distraction during medical procedures, such as chemotherapy or wound care.…”
Section: Developmentmentioning
confidence: 99%